Identificação molecular e caracterização de cepas isoladas do resíduo de bauxita - Nogueira, Elis Watanabe (2015)
This study aimed to identify and characterize three strains BRA1, BRA3 and BRA5 isolated from bauxite residue in the Southern region of Minas Gerais. Sequencing of 16S ribosomal RNA gene was carried out using two pairs of primers, which allowed high quality sequencing of 1300pb from each isolated strain. Additional biochemical tests were conducted to characterize the strains. The results indicated that strain BRA1 was identified with 99.7% similarity with B. cohnii and characterized as: Gram-positive; positive for nitrate reduction, catalase, oxidase and amylase; growth range between pH 7 and 10; tolerant to concentrations of 0 to 10% NaCl, and; growth is observed between 20 and 40 °C. The strain BRA3 was identified with 99.7% similarity with Bacillus pseudofirmus and characterized as: Gram-positive; positive for catalase and amylase; negative for oxidase and nitrate reduction; growth range between pH 7 and 10; tolerant to concentrations of 5 to 10% NaCl, Na+ ion dependent for growth, and; growth is observed between 10 and 40 °C. In the results of the sequencing analysis, strain BRA5 was identified with 99.7% similarity with Bacillus clarkii and Bacillus polygoni. After biochemical and physiological tests, the strain BRA5 was closest to the biochemical characteristics of Bacillus clarkii, characterized as Gram-positive; positive for catalase and oxidase, non-nitrate reduction, and amylase; growth range between pH 8 and 10; tolerant to concentrations of 5 to 10% NaCl, Na + ion dependent for growth, and; growth is observed between 20 and 40 °C. The use of sugars: glucose, fructose, sucrose and mannitol was positive and the higher amount of acids produced from the carbon sources were acetic, isobutyric, isovaleric, among others. Strains BRA1, BRA3 and BRA5 using glucose as a carbon source were able to decrease the medium pH 10.5 to approximately 9.3, 9.5 and 9, respectively. The identification and characterization of isolates were successful and the results presented are consistent with those found in the literature.